Individual Factors Influence Incidence Of Low Back Pain In Batik Craftsman - Nadila Putri Pramesti; Hidayat Kussugiharso Wibowo; Prima Maharani Putri (Jurnal Keterapian Fisik, 2021)
Background: The incidence of low back pain in Indonesia is still relatively high with an injury prevalence of 6.5%. One of the contributor of the high incidence rate is caused by occupational factors such as works that are repetitive in nature, that imposes forced power, and static work. One of the job that poses this risk is batik craftsmen. It is estimated that there are 15.000 batik craftsmen who are actively working in Central Java Province. The aim of study was to determine association between individual factors and incidence of low back pain in batik craftsman. Methods: This study is a quantitative study with cross-sectional design, conducted in February 2021 in Central Sokaraja Village. Sample collection was carried out with total sampling method with a total sample of 60 respondents. Data analysis technique used in this study was Chi square test Results: The result of Chi square test showed that there is a significant association between work period and low back pain (p=0.001), there is a significant association between sitting duration and low back pain (p=0.028), there is a significant association between work load and low back pain (p=0.002), there is no significant association between gender and low back pain (p=0.081), there is no significant association between age and low back pain (p=0.632), and there is no significant association between body mass index and low back pain (p=0.807). From multivariate analysis, it was found that there is a significant association between work period and low back pain (p=0.026). Conclusion: There is a significant association between work period, sitting duration, and work load with low back pain, while there is no significant association between age, gender and body mass index (BMI) with low back pain.